THE SERVICE MIND ACCORDING TO BUDDHIST CONCCPTS OF THE PEOPLE BAN BANGNOD COMMUNITY KHANOM SUB-DISTRICT KHANOM DISTRICT NAKHON SI THAMMARAT PROVINCE - Supatittito (Khemthong), Phra Sarawut; Nunklam, Direk; Nuthongkaew, Kantaphon (Journal of MCU Nakhondhat, 2022)
The objectives of this research article were to: 1) study the mobilization of volunteer spirit and 2) study the recommendations on the guideline to drive Buddhist volunteerism of the people in Ban Bang Nod community, Khanom sub-district, Khanom district, Nakhon Si Thammarat province. The population used in this study were residents of Ban Bang Nod Community, Khanom Sub-district, Khanom District, Nakhon Si Thammarat Province. It is a combined research method. It consists of quantitative research. Data were collected using questionnaires and qualitative research. Collect data by interviewing key informants. The results of the research were as follows: 1. The overall level of Buddhist volunteering in Ban Bang Nod community, Khanom district, Nakhon Si Thammarat province was averaged at a high level ( = 4.01). Buddhist Volunteer Movement There is a suggestion that It should encourage and encourage the next generation to have a conscience and do good deeds for society. by applying Dharma principles as a basis to create a conscience of doing benefits for individuals, communities, and societies without expecting anything in return promote unity to help and support each other, cultivate a conscience for people in the society to have mercy. Please continue to join the world encourage people in the area to adopt the doctrine Religious that meets the ethics of people in society Increasing the opportunity to work in volunteering, encouraging volunteering to have a neutral mind that does not discriminate. Do not choose nepotism by without bias, joint thinking, working together to solve problems, working as a team, leading to the movement of Buddhist volunteerism to become concrete towards individuals, communities, society, and the nation.